INCORPORATING TECHNOLOGY IN GRAMMAR INSTRUCTION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: In the fast-paced world of education, it's essential to keep up with the latest tools and methodologies to enhance the learning experience for students. When it comes to teaching grammar, integrating technology can be a game-changer. In this article, we'll explore the benefits and strategies of incorporating technology in grammar instruction, shedding light on how it can revolutionize the way we approach language education.